2015
DOI: 10.1007/s11356-015-5440-4
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and spatial variations of greenhouse gas fluxes from a tidal mangrove wetland in Southeast China

Abstract: Tidal mangrove wetlands are a source of methane (CH4) and nitrous oxide (N2O); but considering the high productivity of mangroves, they represent a significant sink for carbon dioxide (CO2). An exotic plant Spartina alterniflora has invaded east China over the last few decades, threatening these coastal mangrove ecosystems. However, the atmospheric gas fluxes in mangroves are poorly characterized and the impact of biological invasion on greenhouse gas (GHG) fluxes in the wetland remains unclear. In this study,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
32
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(39 citation statements)
references
References 58 publications
7
32
0
Order By: Relevance
“…High temperatures in summer are favourable for physiological processes in soil microbial processes, and plant respiration. This effect of temperature is supported with the research by Pulliam (1993) and Wang et al, (2016), from which they found that high temperatures promote the oxidative breakdown of organic matter and plant tissue (root and shoot) respiration. In a related study, it was found that wetlands act as sources of CO 2 if climate, hydrologic conditions and soil temperatures enhance oxidation of organic matter and root respiration (Altor & Mitsch, 2008).…”
Section: Seasonal Variation Of Environmental Factorssupporting
confidence: 64%
“…High temperatures in summer are favourable for physiological processes in soil microbial processes, and plant respiration. This effect of temperature is supported with the research by Pulliam (1993) and Wang et al, (2016), from which they found that high temperatures promote the oxidative breakdown of organic matter and plant tissue (root and shoot) respiration. In a related study, it was found that wetlands act as sources of CO 2 if climate, hydrologic conditions and soil temperatures enhance oxidation of organic matter and root respiration (Altor & Mitsch, 2008).…”
Section: Seasonal Variation Of Environmental Factorssupporting
confidence: 64%
“…Vegetated habitats typically have higher sediment OM concentrations compared to sediments without vegetation (e.g., Banerjee et al, 2018; Marinho, Campos, Guimarães, & Esteves, 2012; Yuan et al, 2015). Generally, there is a reported increase in CH 4 emissions in vegetated compared to nonvegetated areas (e.g., Bahlmann et al, 2015; Wang et al, 2016). When plants are photosynthesizing, they deposit labile OM into the sediment around their roots or rhizosphere (Blaabjerg & Finster, 1998; Holmer, Andersen, Nielsen, & Boschker, 2001), thereby providing a substrate to stimulate CH 4 production (Bridgham et al, 2013).…”
Section: Driversmentioning
confidence: 99%
“…Although the impact of plant species on soil microbial communities is widely documented16710262841, few studies have been performed on tree-associated microbial communities. However, such surveys are essential because by modifying the soil chemistry (pH, nitrogen and cations availability) and microbial biomass and activity, trees have a long-term impact on the environment compared to plants with a shorter lifetime82742.…”
Section: Discussionmentioning
confidence: 99%